PERINGKAT KINERJA LEMBAGA KEUANGAN SYARIAH BERDASARKAN MAQASHID SYARIAH - Herni Ali HT; Ali Rama (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This study aims at developing the concept of maqashid al-shari’ah as the fundamental principles for sharia banks. It also sought to develop measurement methods through relevant performance ratio. Maqashid al-shari’ah principles are underlined by three major concepts, namely: (i) individual learning (tahdhibal-fard); justice enforcement (iqamah al-‘adl); and welfare improvement (jalb al-maslahah). These three concepts are then derived into measurable dimentions, elements, an d indicators for public sharia banks in Indonesia. This study employed indexation and benchmarking to 2014 financial report and it found that there is no correlation between the sharia bank assets to their maqashid al-shari’ah performance. Bank Syariah Mandiri with the biggest asset, for instance, perfomed low in the principle of maqashid al-shari’ah. On the contrary, Bank Maybank Syariah and Panin Syariah with less assets performed better. This study suggests that sharia banks Indonesia should apply maqashid al-shari’ah principles for the organizational goals and evaluation method. KEY WORDS:Maqashid al-shari’ah, financial performance, individual learning, justice, welfare, sharia banks